2018
DOI: 10.1111/hsc.12703
|View full text |Cite
|
Sign up to set email alerts
|

Why are they reluctant to report? A study of the barriers to reporting to child welfare services among public dental healthcare personnel

Abstract: This study is a national cross-sectional survey, conducted in November 2014, of 366 dental hygienists and dentists who had suspected maltreatment but did not report it to Norwegian Child Welfare Services (CWS). The aims of the present paper are to identify the reasons why public dental healthcare professionals are reluctant to report suspected child maltreatment to CWS and to determine whether there are differences in the identified barriers according to socio-demographic variables. The questionnaire was based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Uncertainty regarding potential maltreatment is known to be a major risk factor for inconsistent reporting to CPS by healthcare professionals. [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty regarding potential maltreatment is known to be a major risk factor for inconsistent reporting to CPS by healthcare professionals. [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, even if participants reported suspicion for maltreatment, only 80% chose to report to CPS. Even though 80 % seem to be a high percentage in a system without mandatory reporting, it has to be considered that known barriers for reporting, such as familiarity with the family [ 20 ], fear of negative consequences of a report for oneself, the patient or the family [ 19 ] and uncomfortability with addressing the issue of maltreatment with the family [ 21 ] may be a minor obstacle in a theoretical case vignette compared to real life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the nurse assistants in the study never made a maltreatment report out of concern that they might not recognize signs of maltreatment. In a Norwegian study of dentists and dental hygienists, over 90% of respondents identified uncertainty about their assessment about child abuse and neglect as a reason for not reporting, followed by not having enough knowledge about child maltreatment and not being sure how to report (Bjørknes et al 2019).…”
Section: Struggling With Identifying Child Maltreatment or With The Rmentioning
confidence: 99%
“…Often professionals are reluctant to report out of fear of damaging their relationships with children or parents, anxiety for their own safety, or concerns about involvement in legal proceedings (Alvarez et al 2004;Bjørknes et al 2019;Falkiner et al 2017;Flaherty 2015;Golomb et al 2016;McTavish et al 2017;Svärd 2017). Mental health professionals and counselors face the dilemma of violating clients' trust or confidentiality when they make a report (Golomb et al 2016).…”
Section: Fear Of Consequences Of Reportingmentioning
confidence: 99%
See 1 more Smart Citation